EDUKASI PEMBUATAN LILIN AROMATERAPI DARI MINYAK JELANTAH DI SMA NEGERI 1 PRACIMANTORO WONOGIRI - Agung Setyarini; M. Fathul Anwar; Nugraheni Retnaningsih (LPPM Universitas Bina Bangsa, 2024)
Used cooking oil is an oil that has been used repeatedly. This used cooking oil waste is harmful to health and is one of the sources of environmental pollution. The partners of this activity are students of SMAN 1 Pracimantoro Wonogiri. The purpose of this community service activity is to provide knowledge and understanding of the impact of the use and disposal of used cooking oil, provide information and knowledge about products that can be produced from used cooking oil waste, namely aroma therapy candles, and improve soft skills by making aroma therapy candles. The methods used are counseling and training. The form of activities is in the form of counseling and training. The methods used are lectures, demonstrations and exercises. Participants first listened to the material delivered by the community service team, then were trained to make aromatherapy candles from used cooking oil waste. The response of the participants to this activity was positive, this was shown by the enthusiasm of the participants in the discussion during the counseling. The result of the activity was an increase in knowledge about the dangers of using used cooking oil, environmental pollution, and skills in making products from used cooking oil waste management in the form of aromatherapy candles by 12.2%